2000
DOI: 10.1111/j.1479-828x.2000.tb03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after Caesarean section: an Australian multicentre study

Abstract: Retrospective analysis of medical records and individual case review was undertaken at 11 major obstetric hospitals for a 5 year period from July 1992 to June 1997 to investigate rates of vaginal birth after Caesarean section (VBAC), the occurrences of uterine rupture, and the outcomes for mother and infant following rupture. Total deliveries were 234,015, of which 21,452 or 9.2% were associated with one or more previous Caesarean sections. Within this scar group, 5419 patients or 25.3% were delivered vaginall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
2
27
1
Order By: Relevance
“…14 There are variations in the reported incidence of scar rupture across units. Large studies in Scotland (n=35,854) 7 and Australia (n=21,452) 13 reported uterine rupture rates of 0.35% and 0.3%, respectively. A large study 8 (n=20,095) in the United States gave a scar rupture rate of 0.52% among women with spontaneous onset of labour (relative risk compared with elective CS, 3.3; 95% confidence interval, 1.8 to 6.0).The true incidence of scar rupture could be difficult to ascertain: some ruptures will pass undetected, and what some would call a rupture others may classify as a 'dehiscence', and this word is not always taken as synonymous with rupture.…”
Section: Risk Of Scar Rupturementioning
confidence: 97%
See 1 more Smart Citation
“…14 There are variations in the reported incidence of scar rupture across units. Large studies in Scotland (n=35,854) 7 and Australia (n=21,452) 13 reported uterine rupture rates of 0.35% and 0.3%, respectively. A large study 8 (n=20,095) in the United States gave a scar rupture rate of 0.52% among women with spontaneous onset of labour (relative risk compared with elective CS, 3.3; 95% confidence interval, 1.8 to 6.0).The true incidence of scar rupture could be difficult to ascertain: some ruptures will pass undetected, and what some would call a rupture others may classify as a 'dehiscence', and this word is not always taken as synonymous with rupture.…”
Section: Risk Of Scar Rupturementioning
confidence: 97%
“…This is not a risk that materializes often, but when it happens the woman may suffer massive bleeding, blood transfusion, loss of her womb or compromised reproductive future, and the baby may die or suffer hypoxic brain injury. 13 These are serious complications that the woman should be warned of well in advance. 14 There are variations in the reported incidence of scar rupture across units.…”
Section: Risk Of Scar Rupturementioning
confidence: 99%
“…The incidence of uterine rupture is 0.2-1.5% in women who attempt labor after a transverse lower uterine segment incision [14,16,18,27,45] and 1-1.6% in women who have had a vertical incision in the lower uterine segment [46][47][48][49]. The risk is 4-9% with a classical or bTQ incision; thus TOL after Caesarean is contraindicated in these situations [16,19,30].…”
Section: Uterine Rupturementioning
confidence: 93%
“…Several other smaller studies reported that it appeared to be safe, effective, and not associated with an increased risk of uterine rupture [45,[64][65][66].…”
Section: Inductionmentioning
confidence: 95%
“…As recently as 2000, the Australian vaginal birth after caesarean section (VBAC) study group found that only one quarter of women with a previous caesarean scar had a vaginal delivery. 37 This is despite the known low risk of uterine rupture in VBACs. As noted by Robson and de Costa, the issue of offering a trial vaginal delivery after a previous caesarean section '... illustrates beautifully the essential tension between evidence-based practice and patient choice and autonomy'.…”
Section: The Twentieth Century and Beyondmentioning
confidence: 96%